Spatial Variation of Water Quality Parameters in Gebeng Industrial Area, Pahang, Malaysia - Islam, Mir Sujaul; Hossain, Mohamed Amjed; Sobahan, Md Abdus; Zularisam, A. W.; Edriyana, Abd Aziz (IACSIT Press, Singapore, 2012)
The study was conducted to examine the physico-chemical parameters of surface water quality in the Gebeng Industrial area, Pahang, Malaysia. Water samples were collected monthly from the selected 10 sampling site in the study area. The selected parameters were analyzed based on in-situ and ex-situ analysis according to standard methods. The statistical software was used for data analyses. It was observed that, the non-point source pollutants were associated with runoff from construction sites of newly developed industrial areas and the point source contributing the major pollutants especially from industrial wastes. Low levels of dissolved oxygen (DO) and higher levels of chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), ammoniacal nitrogen and selected heavy metals made the water pollution. According to Interim National Water Quality Standard (INWQS), the major part of the river specially the mid-region was categorized as class V (very highly polluted) while some part was found to be in class IV (highly polluted) and rest of class III (polluted) as well. Based on Malaysian Water Quality Index (WQI), the most stations except lower and uppermost were in class IV, and highly polluted.